2021
DOI: 10.1021/acs.jmedchem.0c00727
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-Catalyzed Nitrile-Addition/N-Arylation Ring-Closure Cascade: Synthesis of 5,11-Dihydro-6H-indolo[3,2-c]quinolin-6-ones as Potent Topoisomerase-I Inhibitors

Abstract: In this paper, we present a copper­(I)-catalyzed nitrile-addition/N-arylation ring-closure cascade for the synthesis of 5,11-dihydro-6H-indolo­[3,2-c]­quinolin-6-ones from 2-(2-bromophenyl)-N-(2-cyanophenyl)­acetamides. Using CuBr and t-BuONa in dimethylformamide (DMF) as the optimal reaction conditions, the cascade reaction gave the target products, in high yields, with a good substrate scope. Application of the cascade reaction was demonstrated on the concise total syntheses of alkaloid isocryptolepine. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Eighteen isocryptolepine-triazole analogs (11 a-11 r) were prepared to evaluate for their cytotoxic activities. [30][31][32][33][34][35][36][37] In vitro cytotoxic evaluation…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen isocryptolepine-triazole analogs (11 a-11 r) were prepared to evaluate for their cytotoxic activities. [30][31][32][33][34][35][36][37] In vitro cytotoxic evaluation…”
Section: Resultsmentioning
confidence: 99%
“…It was worth mentioning that substrates 1 g , 1 p , 1 aa bearing a nitro group were also feasible in this reaction and provided the desired products 2 g , 2 p , 2 aa in 69 %, 59 %, 53 % yields respectively. These results indicated that the possible interaction of nitro group with Cu(I) intermediates did not show any detrimental effect to this transformation [25a–b] . Furthermore, multi‐functionalized substrates containing dibromo, dimethoxyl and trimethoxyl groups were workable under the standard conditions, giving the desired products 2 t , 2 u , 2 v , 2 w in 46 %–79 % yields.…”
Section: Resultsmentioning
confidence: 74%
“…The interaction of 14 with the top1–DNA complex was next revealed by a docking simulation on a top1–DNA–drug ternary complex (PDB 1TL8) using HCPT and 1 as controls (Figures E and S12). The poses of 14 and HCPT with the lowest energy in the complex were identified and were similarly stacked in the DNA cleavage site formed by the TPC11–G112 and T10–A113 base pairs, with a likely π–π stacking interaction formed through its anthraquinone ring. The C-9 carbonyl group in 14 may serve as a hydrogen bond acceptor for Arg364, while its ethyl side chain interacts with Thr718 through certain hydrophobic interactions.…”
Section: Results and Discussionmentioning
confidence: 99%